Elaboración de un plan de mantenimiento predictivo para el puente grúa de la nave número dos de la bodega de almacenamiento de producto terminado de la Industria Novacero S.A Planta Lasso. - Cruz Cajas, Stefy Monserrat (2018)
The present research project consists in the elaboration of a predictive maintenance plan in the warehouse. Number of storage warehouses of the finished product of the company Novacero S.A plant in Lasso province of Cotopaxi. The purpose of this project is to optimize the process of dispatching the finished product, to ensure that the thick bridges of the aforementioned area meet their working hours without any interruption. A predictive maintenance schedule for the execution of the analysis of this type of maintenance has been found, which can already corroborate to verify failures that occur constantly in the bridge cranes, with the purpose of corrective maintenance costs, to take advantage of the useful life of the machine and to avoid the work accidents for the operators of the bridges in the aforementioned company. A thermographic analysis and a vibration analysis were carried out to determine the damage of the bridge crane and anticipate the mechanical failures that may interrupt the operation of the bridge and the realization of a checklist to establish the critical points of the bridge crane parts. that need to be examined periodically verifying their status and if they will need repairs or changed by new parts in order to maintain the useful life of the bridge that allow the constant process of dispatching to customers.